Evaluating ecosystem goods and services after restoration of marginal upland peatlands in South‐West England. Issue 2 (19th February 2013) - Grand‐Clement, Emilie; Anderson, Karen; Smith, David; Luscombe, David; Gatis, Naomi; Ross, Martin; Brazier, Richard E.; Wan, Shiqiang
Summary In the UK, drainage for agricultural reclamation during the 19th and 20th centuries is responsible for an alteration of the ecological and hydrological functioning of peatlands, in turn, affecting a whole suite of ecosystem services. Today, initiatives are in place throughout the UK to reinstate this eco‐hydrological functioning by blocking drainage ditches. Effects on ecosystem services remain unclear, as does the overlapping impact of climate change on peatland recovery. This article uses a conceptual model to present the effects of restoration on ecosystem services, that is, water provision and quality, carbon storage, biodiversity, food and fibre provision and cultural services, both immediately after ditch blocking and in the few years post‐restoration. The model is then applied in the context of Exmoor National Park, in South West England and used to perform a cost–benefit analysis of the restoration and monitoring programme, as these shallow peatlands are located in geographically marginal areas, and therefore more sensitive to climate change. Past research indicates that some processes tend to return progressively to their predisturbance state, but whether the complete recovery of peatlands to functioning mires occurs after restoration remains unclear, partly due to the difference between the temporal and spatial scale at which processes occur (i.e. up to decadal) and are monitored (typically a few years). Overall, on Exmoor, the long‐term benefit of peatland restoration to some ecosystem services, such as a reduction in carbon losses and improvement of water storage and quality, has the potential to balance high financial investment. Synthesis and applications. Gaining a better understanding of the effects of peatland restoration on ecosystem services provided is essential to assess the potential value of restoration projects. Using the case of the shallow peatlands of Exmoor National Park, located in geographically marginal areas in the UK and therefore more vulnerable to the effects of climate change, we find that there is potential for both the value of carbon storage and water provision to offset the costs of restoration in the long‐term. Our results from Exmoor can provide ecological analogues of impending change further north.